The Incidence of Comorbidities in New Adult Tuberculosis Cases - I. R. Gudieva; B. M. Maliev; N. V. Kobesov; O. Z. Basieva; S. A. Sterlikov (Туберкулез и болезни лёгких, 2023)
The objective: to determine the potential impact of particular nosologies and their groups on the risk of developing tuberculosis.Subjects and Methods. The incidence of particular nosologies and their groups standardized by gender and age in new tuberculosis cases detected in 2020 was compared to the general incidence of those nosologies among population of RNO-Alania. Relative risk (RR) and statistical significance of differences (p) were determined.Results. RR of type I diabetes mellitus (DM) in tuberculosis patients to the overall incidence of the entire population was 9,5 (p<0,001); RR of viral hepatitis – 6,4 (p<0,001); mental disorders – 3.2 (p<0,001); type II DM – 2,6 (p<0,001); chronic nonspecific lung diseases (CNLD) – 2,3 (p=0,005). There was no excess of RR for digestive diseases (RR=0,9; p=0,9). The role of genitourinary diseases could not be verified due to the lack of observations.